PENGARUH KOMUNIKASI INTERNAL DAN KOMUNIKASI INTERPERSONAL TERHADAP KEPUASAN KERJA ANGGOTA POLRI POLSEK SAWAN - Kadek Widana; Ni Luh Sayang Telagawati (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aim to examine the influence of (1) internal communication on job satisfaction (2) internal communication on job satisfaction (3) internal communication and interpersonal communication on job satisfaction. The subjects in this study were POLRI members at the Sawan Police. The objects in this study were internal communication, interpersonal communication, and job satisfaction of POLRI members at the Sawan Polsek. The population in this study were all POLRI members at the Sawan Polsek, totaling 57 people. The method used in this research is to use a descriptive quantitative method. Where in this descriptive quantitative research, the data collected is in the form of numbers which are the result of distributing questionnaires to the sample (respondents). The sample in this study is all members of the population or is a saturated sample. This research is also a type of causal quantitative research. Where this study aims to determine the causal relationship arising from the independent variables on the dependent variable. The data obtained was then processed using multiple linear regression analysis models with the help of SPSS 22 software. The results of the research using the 't' test showed that the value of the internal communication variable wast count 2.702 > t table 2.005 and the interpersonal communication variable shows a value of t count 4.718 > t table 2.005. Then based on the results of the 'f' test that was carried out, the results were obtained forf count 76,978 < 3,165 f table.Furthermore, based on the results of calculations using multiple linear regression analysis, the coefficient results obtained from the job satisfaction variable were 7.258 and the coefficients from the internal communication and interpersonal communication variables were 0.312 and 0.548 respectively. With an Adjusted R Square determinant coefficient of 0.731. From the results of these calculations, conclusions can be drawn in the form; (1) internal communication has a positive and significant effect on job satisfaction, (2) interpersonal communication has a positive and significant effect on job satisfaction, (3) internal communication and interpersonal communication has a positive and significant effect on job satisfaction by 73% while the remaining 27% is explained by other variables not examined in this study.